Compensación Electrónica de la Dispersión en Fibras Ópticas Usando el Conjugado de Fase Óptica - García-Pérez, Arturo; Ramírez-Gasca, Humberto; Andrade-Lucio, José Amparo; Ibarra-Manzano, Oscar Gerardo; López-Hernández, Juan Manuel; Sukhoivanov, Igor Alexander; Trejo-Duran, Mónica (Acta Universitaria, 2009)
The topic of this work will deal with the investigation of a novel electronic dispersion compensation technique in long-haul fiber optic communications, in which a signal is electricalpre-compensated using a differential Mach-Zender modulator, driven by nonlinear digital filters. The chromatic dispersion was effectively compensated for by using an optical phase conjugation in the transmitter, through 4000 Km of standard single mode fiber (with non onlinearity and attenuation), where the dispersion is compensated for a 10 Gb/s intensity modulated NRZ (non-return to zero) signal. The dispersion compensation was confirmed by measuring bit error rate and observing detected eye diagrams.
Keywords: Array; Array; Array; Array